The Development of EduPlasa Media Learning Devices in Static Fluid Materials - Humaira, Haifa; Halim, A; Wahyuni, Agus (Asian Journal of Science Education, 2019)
This study aims to develop learning devices for EduPlasa media in static fluid material. The research method used is descriptive method with a quantitative approach. The research subjects were students of class XI MIPA 4, amounting to 24 people in state senior high school Banda Aceh. Data collection techniques in the form of questionnaires validation media experts, content and learning tools and documentation. The results of the study indicate that the learning device for EduPlasa media is effectively used. This can be seen from the results of the percentage of media rated by experts at 81.5%, the percentage of media content assessed by experts as much as 85% and the responses of students about the media reached 86.68% so that the media can be said to be suitable for use in learning. Development of learning tools for EduPlasa media in the form of learning implementation plans (RPP), student worksheets (LKPD), power points as supporters of interactive media. The results of validation by evaluation experts and practitioners for RPP and LKPD obtained an assessment of 75% so that the learning device met the criteria of valid, practical and effective use.